Heterogeneous acid-base organocatalyst for cascade deacetalisation-knoevenagel condensations - Chhetri, Ashis; Maibam, Ashakiran; Maniam, Subashani; BabaRao, Ravichandar; Wilson, Karen; Lee, Adam F.; Mitra, Joyee (ChemSusChem, 2024)
Multifunctional heterogeneous catalysts are an effective strategy to drive chemical cascades, with attendant time, resource and cost efficiencies by eliminating unit operations arising in normal multistep processes. Despite advances in the design of such catalysts, the fabrication of proximate, chemically antagonistic active sites remains a challenge for inorganic materials science. Hydrogen-bonded organocatalysts offer new opportunities for the molecular level design of multifunctional structures capable of stabilising antagonistic active sites. We report the catalytic application of a charge-assisted, hydrogen-bonded crystalline material, bis(melaminium)adipate (BMA), synthesised from melamine and adipic acid, which possesses proximate acid-base sites. BMA exhibits high activity for the cascade deacetalisation-Knoevenagel condensation of dimethyl acetals to form benzylidenemalononitriles under mild conditions in water; BMA is amenable to large-scale manufacture and recycling with minimal deactivation. Computational modelling of the melaminium cation in protonated BMA explains the observed catalytic reactivity, and identifies the first demethoxylation step as rate-limiting, which is in good agreement with time-dependent 1H NMR and kinetic experiments. A broad substrate scope for the cascade transformation of aromatic dimethyl acetals is demonstrated.
Keywords: Antagonistic acid-base sites; Charge-assisted hydrogen bonding; Chemical cascade; organocatalysis; Sustainable catalysis

Ru/MgO-catalysed selective aerobic oxidation of 5-hydroxymethylfurfural to 2,5-furandicarboxylic acid - Lokhande, Priya; Dhepe, Paresh L.; Wilson, Karen; Lee, Adam F. (Australian Journal of Chemistry - an International Journal for Chemical Science, 2024)
Biomass valorisation through the selective oxidation of carbohydrate and lipid derivatives offers access to an array of platform chemicals through energy- and atom-efficient catalytic processes. Supported metal nanoparticles are promising catalysts for the aerobic selective oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA), but typically require strong liquid base to achieve high selectivity. Here, we explore the utility of MgO as a solid base support for the Ru-catalysed aerobic oxidation of HMF, obtaining 68% FDCA yield at 160°C and 1.5 MPa of O<span style="box-sizing: inherit; font-size: 11.25px; line-height: 0; position: relative; vertical-align: baseline; bottom: -0.25em; color: rgb(0, 49, 60); font-family: "Open Sans", sans-serif; background-color: rgb(241, 250, 244);">2 using <1 mol-% metal.